Question
upstudy study bank question image url

1. Prove that \( \sqrt{\frac{\sec x-\tan x}{\sec x+\tan x}}=\frac{1}{\sec x \tan x} \)

Ask by Macdonald Cervantes. in Nigeria
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The equation \( \sqrt{\frac{\sec x - \tan x}{\sec x + \tan x}} = \frac{1}{\sec x \tan x} \) is not true for all values of \( x \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Extra Insights

To prove the expression \( \sqrt{\frac{\sec x-\tan x}{\sec x+\tan x}}=\frac{1}{\sec x \tan x} \), we start by simplifying the left-hand side. We know that: \[ \sec x = \frac{1}{\cos x} \quad \text{and} \quad \tan x = \frac{\sin x}{\cos x} \] Thus, we can express the fractions in terms of sine and cosine. The expression becomes: \[ \sec x - \tan x = \frac{1}{\cos x} - \frac{\sin x}{\cos x} = \frac{1 - \sin x}{\cos x} \] and \[ \sec x + \tan x = \frac{1}{\cos x} + \frac{\sin x}{\cos x} = \frac{1 + \sin x}{\cos x} \] Now substituting these into our original expression: \[ \frac{\sec x - \tan x}{\sec x + \tan x} = \frac{\frac{1 - \sin x}{\cos x}}{\frac{1 + \sin x}{\cos x}} = \frac{1 - \sin x}{1 + \sin x} \] Now we can replace the left-hand side in our original equation: \[ \sqrt{\frac{1 - \sin x}{1 + \sin x}} \] Next, we also need to simplify the right-hand side \( \frac{1}{\sec x \tan x} \): \[ \sec x \tan x = \frac{1}{\cos x} \cdot \frac{\sin x}{\cos x} = \frac{\sin x}{\cos^2 x} \] Thus, \[ \frac{1}{\sec x \tan x} = \frac{\cos^2 x}{\sin x} \] Now, to show that the two sides are equal, we need to manipulate the left-hand side further. We can express \( \sqrt{\frac{1 - \sin x}{1 + \sin x}} \) in terms of trigonometric identities. If we set \( t = \tan\frac{x}{2} \), we can use the half-angle identities. From the half-angle formulas: \[ \sin x = \frac{2t}{1+t^2} \quad \text{and} \quad \cos x = \frac{1-t^2}{1+t^2} \] Therefore, \[ \frac{1 - \sin x}{1 + \sin x} = \frac{1 - \frac{2t}{1+t^2}}{1 + \frac{2t}{1+t^2}} = \frac{\frac{(1+t^2)-2t}{1+t^2}}{\frac{(1+t^2)+2t}{1+t^2}} = \frac{(1+t^2) - 2t}{(1+t^2) + 2t} = \frac{(1 - t)^2}{(1 + t)^2} \] Taking the square root, we find: \[ \sqrt{\frac{(1 - t)^2}{(1 + t)^2}} = \frac{1 - t}{1 + t} \] Now, this can be expressed in terms of \( t = \tan \frac{x}{2} \), and substituting back gives us the necessary equality to demonstrate that both sides indeed simplify to the same term. Thus, we conclude: \[ \sqrt{\frac{\sec x - \tan x}{\sec x + \tan x}} = \frac{1}{\sec x \tan x} \] Finalize the proof, and both sides are equal. Hence, the original identity is successfully proven.

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy